1986
DOI: 10.1128/iai.52.1.200-204.1986
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to lethal Candida infections in burned mice preinfected with Pseudomonas aeruginosa or pretreated with proteolytic enzymes

Abstract: Lethal Candida infections in burn patients are frequently preceded by or occur concomitantly with bacterial infections, which are often due to Pseudomonas aeruginosa. In this study, we developed a burned, mixed-challenge mouse model, which was designed to determine whether and how a recent bacterial infection could influence the development of subsequent candidosis. In this model, burned mice that were preinfected with a sublethal challenge of elastase-producing P. aeruginosa strain WR-5 and then sublethally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 30 publications
(29 reference statements)
2
31
0
Order By: Relevance
“…This agrees with the findings of earlier studies. 14,18,19 Gupta et al [18] determined 59% Candida species in cases with bacteria infected burn wounds. However, when P. aeruginosa was present, fungal colonisation was significantly inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the findings of earlier studies. 14,18,19 Gupta et al [18] determined 59% Candida species in cases with bacteria infected burn wounds. However, when P. aeruginosa was present, fungal colonisation was significantly inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…25 The presence of Pseudomonas exacerbates tissue damage in a model of Candida infection of burn wounds. 26 Biofilms formed between C. albicans and either S. aureus or S. gordonii are larger and more drug resistant than their monomicrobial counterparts. 24,27 Clearly there are context-dependent interactions that prevent simple conclusions about the in vivo effect of mixed infections.…”
Section: A Nematode Co-infection Model Reveals Surprising Interactionsmentioning
confidence: 99%
“…Patients infected with P. aeruginosa often show evidence of impaired cell-mediated immunity (28,33,34). In support of these clinical findings, Neely et al (25) demonstrated that infection with P. aeruginosa predisposed burned mice to lethal infections with Candida albicans. Two independent groups, Blackwood et al (5) and Petit et al (30), found that mice injected with P. aeruginosa were more susceptible to infection with the intracellular pathogen Listeria monocytogenes and showed a decrease in delayed-type hypersensitivity to Listeria and erythrocyte antigens.…”
mentioning
confidence: 94%